Internet of Things (IoT) Enabled Automation in Agriculture - Singh, Rajesh (Taylor & Francis Group, 2022)
This book provides basic knowledge of the programming and interfacing of devices with IoT modem and programming. The aim is to explain the basic steps to understand the IoT and its application in agriculture field
Description based on publisher supplied metadata and other sources